Juridical Review on Corporate Social Responsibility Implementation Between PT Angkasa Pura II (Persero) And Indonesian Flight Navigation Services (LPPNPI) - Yesita Marito; Suyud Margono (Journal of Multidisciplinary Academic, 2021)
The purpose of this study aimed to know the implementation of the Corporate Social Responsibility (CSR) at PT. Angkasa Pura II (Persero), and Indonesian Flight Navigation Services (LPPNPI). Here, we also need to know the factors inhibiting the implementation of Corporate Social Responsibility in PT. Angkasa Pura II (Persero), and LPPNPI. In this study, we used qualitative method from correspondent from both industries. The results showed that the implementation of the Corporate Social Responsibility (CSR) in PT. Angkasa Pura II (Persero), LPPNPI had one of the Corporate Social Responsibilities in the form of partnership and environment building programs in its capacity as a service company under the protection of State-Owned Enterprises (BUMN). This program prioritized the sustainable soft loan system for small entrepreneurs. The responsibility includes the cost and burdens spent by the company to recompense to the community who indirectly built the company.